SPEECH PRODUCTION OF TOURETTE SYNDROME SUFFERER PORTRAYED IN BRADLEY COHEN CHARACTER IN FRONT OF THE CLASS MOVIE - ANJARWATI, EKA (Jurnal Ilmiah Mahasiswa FIB, 2013)
People use language to communicate to others. However, when the language areas in the brain get injured, the speakers may not express their mind clearly to the hearers. There are many causes of language disorder, one of them is Tourette  Syndrome.  This  study  is  aimed  at  describing  (1)  the  symptoms  of Tourette Syndrome produced by Bradley Cohen in “Front of The Class” movie, and (2) the conditions that worsen the Tourette Syndrome experienced by Bradley Cohen in “Front of The Class” movie.This research applied qualitative approach and document analysis. The research data were taken from the “Front of the Class” movie script and scene that consist of utterances containing Tourette Syndrome produced by Bradley Cohen. The writer used theory proposed by NINDS (National Institute of Neurological Disorder and Stroke, 2012) in analyzing dialogues of Bradley Cohen in the movie script.The finding of the study revealed that there were 46 out of 57 scenes that showed utterances containing speech production problem produced by Bradley Cohen.  Through  this  study,  the  writer  only  found  simple  motor  tics.  The symptoms of Tourette Syndrome showed by Bradley Cohen were tics, tics followed by the presence of eye blinking, throat-clearing, facial grimacing, head jerking and leg jerking. Furthermore, the writer figured out that the symptoms of Tourette  Syndrome  were  getting  worse  when  Bradley  Cohen  was  anxious, stressed, and angry.The writer suggests the next researchers who want to analyze Tourette Syndrome to explore complex motor tics such as coprolalia in order to give more insight about Tourette Syndrome. The next researchers can investigate coprolalia from people who suffer from Tourette Syndrome or other media that show the occurrence of coprolalia such as video or newspaper. Keywords:  Psycholinguistics, Speech Production, Tourette Syndrome, Front of the Class movie, Bradley Cohen